Management of vomplex systems: Modeling the biological pest control - Rafikov, Marat; Balthazar, José Manoel [UNESP]; Von Bremen, Hubertus F. (World Scientific Publishing, 2008)
The aim of this paper is to study the cropping system as complex one, applying methods from theory of dynamic systems and from the control theory to the mathematical modeling of the biological pest control. The complex system can be described by different mathematical models. Based on three models of the pest control, the various scenarios have been simulated in order to obtain the pest control strategy only through natural enemies' introduction. © 2008 World Scientific Publishing Company.
Keywords: Applied biological control; Emergence of global behaviour; Lyapunov characteristic exponents; agricultural procedures; biological pest control; caterpillar; computer simulation; conference paper; control strategy; crop improvement; cropping system; ecosystem; mathematical model; parasitoid; population density; population dynamics; predator prey interaction; priority journal; soybean; systems theory